The Adsorption and Elution of Platinum Group Metals (Pt, Pd, and Au) from Cyanide Leach Solutions using Activated Carbon - Snyders, C.; Mpinga, C.; Bradshaw, S.; Akdogan, G.; Eksteen, Jacques (The South African Institute of Mining & Metallurgy, 2013)
This paper investigates the recovery of platinum group metals (PGMs) from a dilute cyanide leach solution containing base metals, in a manner similar to that used for gold extraction in a typical CIP process, and focuses on both the adsorption and elution stages. The carrier-phase extraction of precious metals using activated carbon offers significant advantages over other processes in terms of simplicity, the high pre-concentration factor, rapid phase separation, and relatively low capital and operating costs. As a sorbent, activated carbon is still by far the most important material because of its large surface area, high adsorption capacity, porous structure, negligible environmental toxicity, low cost, and high purity standards. Adsorption tests were performed on a pregnant alkaline leach solution (0.15 ppm Pt, 0.38 ppm Pd, 0.1 ppm Au) resulting from cyanide extraction performed in column leach tests. The initial adsorption rates of platinum, palladium, and gold were very fast and recoveries of these three metals were approximately 90 per cent after 2 hours and 100 per cent, 97.4 per cent, and 99.9 per cent respectively after 72 hours. The parameters that influence the extraction of PGMs and Au were examined to assess their relative importance during the adsorption process in order to provide the basis for process optimization. The concentration of thiocyanate was not identified as significant factor for PGMs adsorption, while nickel concentration was the most significant extraction process parameter. Base metal cyanide complexes adsorb and compete with the PGM complexes for sites on activated carbon, and while copper adsorption can be minimized by adjusting the residence time, nickel adsorbs at approximately the same rate as that of the PGMs, influencing the loading capacity and adsorption kinetics of the PGMs.The feasibility of eluting platinum and palladium cyanide complexes from activated carbon using an analogue of the AARL process was investigated. Platinum and palladium elute from activated carbon almost to completion in 4 to 5 bed volumes at 80°C, while the elution of gold at this temperature is slow, with a significant amount of gold still to be eluted after 16 bed volumes. Cyanide pre-treatment was found to have a significant influence on PGM elution. Higher cyanide concentration in the pre-treatment step results in more efficient elution up to a point, and experiments suggest the possibility of an optimum cyanide concentration, beyond which elution efficiency starts decreasing.